The Politics of Principle : c - Roux, Theunis (Cambridge : Cambridge University Press, 2013)
Under its first chief justice, Arthur Chaskalson, the South African Constitutional Court built an unrivalled reputation in the comparative constitutional law community for technically accomplished and morally enlightened decision-making. At the same time, the Court proved remarkably effective in asserting its institutional role in post-apartheid politics. While each of these accomplishments is noteworthy in its own right, the Court's simultaneous success in legal and political terms demands separate investigation. Drawing on and synthesising various insights from judicial politics and legal theory, this study offers an interdisciplinary explanation for the Chaskalson Court's achievement. Rather than a purely political strategy of the kind modelled by rational choice theorists, the study argues that the Court's achievement is attributable to a series of adjudicative strategies in different areas of law. In combination, these strategies allowed the Court to satisfy institutional norms of public reason-giving while at the same time avoiding political attack.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).